2021
DOI: 10.3390/app112412133
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Characterization Method for SMC Materials for a Preliminary Selection

Abstract: In electrical machines, laminated steels are commonly adopted as soft magnetic materials, while for permanent magnets, sintered ferrites and NdFeB are the most common solutions. On the other hand, the growing demand for volume reduction with the increment of efficiency leads to the necessity of exploring other magnetic materials able to face the challenge better than the traditional ones. Bonded magnets have been used to replace sintered magnets, obtaining a better use of space and particular magnetic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Electromagnetic shielding for low-frequency applications can be achieved by using high permeable flux shunting material. On the other hand, in the case of high-frequency applications (above 1 MHz), a combination of flux shunting material along with an electrically conducting layer for eddy currents cancellation is preferred [ 27 , 50 ]. A finite element simulation is performed to estimate the shielding effectiveness with the use of the pure iron material (manufactured in the present study) along with two types of conducting material (aluminum and copper with 1 mm-thick iron and conducting material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromagnetic shielding for low-frequency applications can be achieved by using high permeable flux shunting material. On the other hand, in the case of high-frequency applications (above 1 MHz), a combination of flux shunting material along with an electrically conducting layer for eddy currents cancellation is preferred [ 27 , 50 ]. A finite element simulation is performed to estimate the shielding effectiveness with the use of the pure iron material (manufactured in the present study) along with two types of conducting material (aluminum and copper with 1 mm-thick iron and conducting material).…”
Section: Resultsmentioning
confidence: 99%
“…Magnetometric and inductive methods are used for the characterization of magnetic materials. The magnetometric methods, including vibrating sample magnetometer (VSM) test, are not suitable for the determination of the hysteresis and initial magnetization curves of high permeable materials such as pure iron and electrical steel, due to the demagnetizing effect on the test specimen [ 27 ]. On the other hand, inductive methods as per IEC60404-4 are preferred for the determination of the hysteresis loop and initial magnetization curve of high permeable soft magnetic materials, including that of the pure iron.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their use, the destruction the material's internal structure, resulting from the implementation of the mechanical laser cutting process (manifested by the deterioration of the material's magnetic prop ties), is avoided. Referring to additive manufacturing methods, a group of works descr ing research conducted on sintered materials can be identified [8][9][10][11][12][13][14][15], as well as a gro of works depicting the research results using laser powder bed fusion technology As the published research results on SMC and LPBF materials indicate, they can be us mainly in motors operating at frequencies of kHz and higher. Then, the low specific ir loss of the material about the Fe-Si laminates, which the authors of this article deal w Hence, there is a common interest in both the problem of the exact description of core losses and the search for methods to reduce them.…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic coating provides long-lasting, high-quality protection against corrosion, scratches, and cracks [1,2]. Heat-treated phenolic coatings can be used in a wide range of acidic environments, even highly acidic environments, as they have excellent acid chemical resistance even at high temperatures [3,4]. Thus, phenolic coatings are optimal for various industrial applications such as fume hoods, pumps, pipes, and tank linings.…”
Section: Introductionmentioning
confidence: 99%